Gas Exchange and Mechanical Properties of the Lung in Miners with Severe Concomitant Injury - V. V. Moroz; Yu. A. Churlyaev; V. N Kiselev; P. G Sitnikov; L. Yu. Redkokasha (Общая реаниматология)
Objective: to study the specific features of pulmonary gas exchange and mechanical properties in various manifestations of respiratory failure in miners with severe concomitant injury, who have a service length of 10 years or more, in order to optimize respiratory support.Subjects and methods. Pulmonary gas exchange and mechanical properties were studied over time in the presence of respiratory failure (acute lung injury/acute respiratory distress syndrome) in 34 miners and 36 victims (a control group) with severe concomitant injury who had no underground service length. Both groups were matched in age, severity and nature of traumatic lesions and surgical interventions. Pulmonary gas exchange and mechanical properties were evaluated by the following indices: oxygen fraction in an inspired gas mixture; hemoglobin saturation and partial arterial blood oxygen and carbon dioxide tension with the alveolar-arterial gradient being calculated by the oxygen level; oxygenation index; intrapulmonary shunting; statistical compliance and airways resistance.Results. The studies demonstrated that the miners, as compared with the controls, had more pronounced gas exchange changes within 5—7 post-traumatic days; later on (days 7—9) the above differences were undetectable. Impaired pulmonary mechanical properties in the miners persisted throughout the study while in the control group, their recovery started just on day 3. The course of respiratory failure in the miners was attributable to the baseline external respiratory function. Their respiratory support was performed during 14.5±1.4 days versus 9.5±1.9 days in the controls. In the miners, the mean bed-days at an intensive care unit were 18.5±2.2 whereas in the controls those were 12.3±2.1.Conclusion. More significant impairments of pulmonary gas exchange and mechanical properties are seen in the miners due to the background changes in external respiratory function in the development of respiratory function after severe concomitant traumatic lesions than in the victims without underground service length, which causes an increase in the duration of respiratory support and intensive care.